KNOWLEDGE PSYCHOLOGISTS SHOULD POSSESS WHEN SERVING AS EXPERT WITNESSES IN COURT - Khushboo Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
Legal systems have developed a variety of procedural mechanisms (such as expert codes of conduct, concurrent evidence, and court-appointed experts) as a response to the threat posed by partisan expert witnesses. These mechanisms aim to help keep experts under control and maintain public trust in the judicial system. These approaches have generated a significant amount of controversy in academic and professional circles, and their adoption by courts has been inconsistent. Despite this, nearly none of the points brought forth in this conversation have been supported by actual study.